Health Literacy in Obstetric Patients: A Pharmacist's Experience with The Newest Vital Sign - Denise Ragland; Nalin Payakachat (MDPI AG, 2015)
Health literacy can greatly impact patients' self-management of medical conditions and adherence to treatment recommendations. This study aimed to assess the health literacy of obstetric patients at a university-based women's clinic using the Newest Vital Sign (NVS). A clinical pharmacist or student pharmacist utilized the instrument to interview women during a routine clinic visit. This project is a cross-sectional, retrospective study using the de-identified survey data. Descriptive statistics were used to provide a summary of the NVS scores in this population. The average age of the 140 participants was 27 years (SD = 6) with the range from 16 to 49 years old. The majority (78%) of the patients was ≤ 30 years old; 50% were white and 39% were black. The average NVS score was 3 (SD = 2.2). 49% had scores ≤ 3 which indicates limited literacy. This pilot study yielded preliminary data for future investigations of health literacy in this population while identifying a potential role for pharmacists. Due to its ease of use and quick administration, it is feasible to use the NVS instrument to routinely screen health literacy in an obstetric clinic setting.